2017
DOI: 10.1177/0898264317726448
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Pathways From Adverse Childhood Experiences to Adult Physical Health: A Structural Equation Model

Abstract: Findings indicate that stress process roles in eroding physical health and experience of wellness. Addressing early adversity is an important strategy toward reducing preventable health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 54 publications
1
42
0
1
Order By: Relevance
“…The importance of examining the significance of child and youth gun violence exposure is underscored by the growing body of literature on both the short-and long-term effects of adverse childhood events (ACEs; Felitti et al, 1998;Nurius, Fleming, & Brindle, 2019;Nurius, Green, Logan-Greene, & Borja, 2015;Schilling, Aseltine, & Gore, 2007;Shonkoff et al, 2011), Recent research has also acknowledged the importance of identifying particularly impactful ACEs that may have been overlooked in child adversity research (Finkelhor, Shattuck, Turner, & Hamby, 2013;Wade, Shea, Rubin, & Wood, 2014) and the need to gain a better understanding of how particular adversities are situated in broader adversity contexts and how different adversities may be interrelated (Barboza, 2018a;Mersky, Janczewski, & Topitzes, 2017). Of particular relevance when considering different forms of gun violence as ACEs is knowledge of the ways that gun violence may overlap with other forms of violence and victimization exposure.…”
mentioning
confidence: 99%
“…The importance of examining the significance of child and youth gun violence exposure is underscored by the growing body of literature on both the short-and long-term effects of adverse childhood events (ACEs; Felitti et al, 1998;Nurius, Fleming, & Brindle, 2019;Nurius, Green, Logan-Greene, & Borja, 2015;Schilling, Aseltine, & Gore, 2007;Shonkoff et al, 2011), Recent research has also acknowledged the importance of identifying particularly impactful ACEs that may have been overlooked in child adversity research (Finkelhor, Shattuck, Turner, & Hamby, 2013;Wade, Shea, Rubin, & Wood, 2014) and the need to gain a better understanding of how particular adversities are situated in broader adversity contexts and how different adversities may be interrelated (Barboza, 2018a;Mersky, Janczewski, & Topitzes, 2017). Of particular relevance when considering different forms of gun violence as ACEs is knowledge of the ways that gun violence may overlap with other forms of violence and victimization exposure.…”
mentioning
confidence: 99%
“…The results of this study suggest that those in the counseling field may benefit from clarity in the definition of ACEs and clients may benefit from counseling scholarship exploring implications of ACEs. Scholars in other fields (CDC, n.d.-b), such as psychology (Blogett & Lanigan, 2018;Hays-Grudo & Morris, 2020) and social work (Cprek et al, 2019;Hunt et al, 2017;Nurius et al, 2019), have begun examining the impact and implications of ACEs for their fields. For example, schools and health practitioners who are considering using screening tools for ACEs would benefit from exploring the ethical implications of doing so (Finkelhor, 2017) within their particular environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Felitti et al (1998) reported that participants with four or more self-reported ACEs were 16.1% more likely to have misused alcohol, 28.4% more likely to have used illicit drugs, 16.7% more likely to have had a sexually transmitted disease, 28.7% more likely to rate themselves in poor health, 4.1% more likely to have experienced a stroke, and 12.2 times more likely to have attempted suicide than a person reporting no ACEs. Although not the first study to examine either the prevalence or impact of youth victimization (see Finkelhor & Dziuba-Leatherman, 1994;Kilpatrick & Saunders, 1997), the Felitti et al study created momentum around the examination of the implications of ACEs for various populations, especially within the medical (Burke et al, Zyromski et al 2011;Choi et al, 2017;Isohookana et al, 2016;Kalmakis & Chandler, 2015), psychology (Blodgett & Lanigan, 2018;Eklund et al, 2018;Sheffler et al, 2019), and social work (Cprek et al, 2020;Nurius et al, 2019) fields. This may have been in part due to both the stark outcomes of the original study and characteristics of the sample (e.g., 79.4% White, 48% male, 43% college educated).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal SEMs were developed by inspecting the significance of constructs' theoretical relevance and path coefficients to fit the data and obtain theoretically sense. lower CSES tend to be surrounded by poorer sanitation, higher burden of disease, less medical service, narrower living space, and even less food availability (41,42), thereby they have worse physical qualities from childhood and suffer higher levels of inflammation related to T2DM (43,44).…”
Section: Sem 10mentioning
confidence: 99%